Inventarisasi tumbuhan mangrove di Hutan Lindung Tanjung Prapat Muda, Kecamatan Batu Ampar, Kalimantan Barat - Handayani, Dea Fitri; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i01.p01, 2024)
Each mangrove ecosystem is diversed which constituted of different vegetations. This also apply for the mangrove area in the Tanjung Prapat Muda Protected Forest, Tanjung Harapan Village, Batu Ampar District. A study of an inventory of mangrove plants was carried out to identify species make up the Tanjung Prapat Muda Protected Forest area. Data collection is conducted alongside the lanes which created by applying the combination of transect and grid lines (transect-plots design). There are 3 lanes with each line consist of 10 plots placed in a zig-zag (right-left) manner. Each plot had sub-plots of different sizes starting from the levels of seedlings (2×2 m), saplings (5×5 m), poles (10×10 m), and trees (20×20 m). Identification was carried out in the field and laboratory. Any unidentified species in the field is documented as herbarium to help identification in the laboratory later. The results shows that there are 7 mangrove species. Five of them are major mangroves (true mangroves), 1 is minor mangrove, and the other 1 are classified as associated mangroves. All the 7 species of plants are belong to  3 families: the Rhizophoraceae, Pteridaceae, and Moraceae families. Five species belong to Rhizophoraceae, namely Rhizophora apiculata , Rhizophora mucronata , Bruguiera gymnorrhiza , Bruguiera parviflora , and Ceriops tagal. The Pteridaceae family consists of one species, namely Acrostichum speciosum , while the Moraceae family only consists of one species, namely Ficus retusa .